Endocrine Aspects of 4H Leukodystrophy: A Case Report and Review of the Literature - Emma Billington; Geneviève Bernard; William Gibson; Bernard Corenblum (Case Reports in Endocrinology)
Introduction. 4H leukodystrophy is an autosomal recessive RNA polymerase III-related leukodystrophy, characterized by hypomyelination, with or without hypodontia (or other dental abnormalities) and hypogonadotropic hypogonadism. Case Presentation. We describe a 28-year-old female who presented with primary amenorrhea at the age of 19. She had a history of very mild neurological and dental abnormalities. She was found to have hypogonadotropic hypogonadism, and magnetic resonance imaging of the brain showed hypomyelination. The diagnosis of 4H leukodystrophy was made. She was subsequently found to have mutations in the POLR3B gene, which encodes the second largest subunit of RNA polymerase III. She wished to become pregnant and failed to respond to pulsatile GnRH but achieved normal follicular growth and ovulation with subcutaneous gonadotropin therapy. Discussion. Patients with 4H leukodystrophy may initially present with hypogonadotropic hypogonadism, particularly if neurological and dental manifestations are subtle. Making the diagnosis has important implications for prognosis and management. Progressive neurologic deterioration is expected, and progressive endocrine dysfunction may occur. Patients with 4H leukodystrophy should be counseled about disease progression and about this disease’s autosomal recessive inheritance pattern. In those who wish to conceive, ovulation induction may be achieved with subcutaneous gonadotropin therapy, but pulsatile GnRH does not appear to be effective.